A review on literature: How information and communication technology (ICT) supports circular economy for sustainable development - Arnezti, Nicky; Ikhsanti, Putri Maziya; Alika, Denisya Ziva; Ummah, Faridatul; Syaukani, R. Candra Ahmad Syaukani; Saputra, Muhammad Akbar; Faisal, Muhammad; Rayza, Muhammad Addif; Ramadhan, Zamsyah Dwi Hushaini (Social, Ecology, Economy for Sustainable Development Goals Journal, 2025)
Background: Information and Communication Technology (ICT) plays a crucial role in enabling the transition to a circular economy. By optimizing supply chain management and fostering innovative circular business models, ICT empowers businesses to reduce waste, conserve resources, and create more sustainable value chains. This research aims to explore the specific ways in which ICT supports the circular economy, including enhanced visibility and traceability, optimized resource allocation, improved collaboration, and the development of circular business models such as product-as-a service and sharing economy. Methods: This paper is qualitative research using Systematic Literature Review (SLR) from 275 papers that contained the relationship between ICT and circular economy as data, included 23 papers reviewed with SLR method. Findings: The result of this research is agreed that ICT has a role in circular economy. This research has explained that ICT can support circular economy through some aspects such as the advance, sustainability, efficiency through technology, etc. Conclusions: By leveraging ICT, businesses can transform their supply chains into circular systems, reducing waste, conserving resources, and creating long lasting value. Novelty/Originality of this article: Combining research from supply chain management and circular business model and the use of SLR method which is still little used.